Antropologia scheletrica virtuale Guida multimediale sulle tecniche fotogrammetriche per la realizzazione di modelli 3D - Lai, Giorgio (UNICApress, 2023)
Virtual skeletal anthropology is of interest for research, education, and communication, particularly in the museum setting. Through images, movies and text, this contribution illustrates the actions and tools required for the creation of 3-D skull models using ultra close range digital photogrammetry (UCR-DP) technique. The procedure is used in the Skeletal Anthropology Laboratory associated with the Sardinian Museum of Anthropology and Ethnography of the University of Cagliari and involves the realization of some steps in cloud mode, freely accessible for study purposes. The protocol is designed for the skull, but can be modified should it be applied to other artifacts (e.g., long bones). Videos describing the procedure in full can be accessed at: https://cinema.dh.unica.it/video-tutorial-3D.